Escola e Família: da semente plantada no chão da escola aos frutos colhidos no quintal de casa. A contribuição da EFA Dom Fragoso à luz da Pedagogia da Alternância - Martins, José Marcone (2019)
This research focuses on the relationship between the family agricultural school Dom Fragoso and the contribution of its pedagogical practice to the families of graduates in their family relationships. The aforementioned institution adopts as teaching methodology the pedagogy of alternation, a pedagogical practice that proposes to offer its students a contextualized education, providing opportunities for the young people of the field to have integral and humanizing formation. This study seeks to understand how the alternation of pedagogical spaces and the pedagogical practice favored the change in the family coexistence of the graduates. Faced with the challenges of the relationship between school and family and an education that contemplates in their identities the peoples of the countryside, we verified at EFA Dom Fragoso A pedagogical practice that achieves this perspective. To know the political project of the school, to study its pedagogical practice and to know the family relationships of the graduates we aim as objectives in this study. The theoretical framework used in the reasoning of the proposed concepts were Gimonet (2007), Begnami (2004), Caldart (2005), Arroyo (2003), Mattos (2011), Freire (2005), Freire (1983). The following documents were also obtained; Laws of national Curriculum Guidelines for Basic Education (2010), the normative Milestones of Field education (2012), the school's Pedagogical political project – PPP and the school's rules of procedure. The qualitative approach was used to use the life history strategy, because it was discussed in phenomena already occurring. In relation to the methodological instruments for the collection of primary data, the use of semi-structured interviews, informal meetings and participant observation was used. The field research was conducted in the community of Santa Luzia with the families of the graduates who reside there, because it is a community with the highest number of graduates from the school. The research revealed a process of change in the family of learners in their relationships. The practice of the school in alternating the pedagogical spaces leads to a coexistence in the dialogue within a contextualized education. This practice has presented itself as a humanizing educative practice, in all contexts of the life of the students.